Identification of reversed portal flow on 4DCT and of factors contributing to reversed portal flow in patients with liver cirrhosis and portosystemic shunt before interventional radiology procedures. Issue 3 (24th November 2022) - Kageyama, Ken; Yamamoto, Akira; Jogo, Atsushi; Sohgawa, Etsuji; Izuta, Shinichiro; Himoto, Daisuke; Kakimi, Akihiko; Kita, Ryuichi; Miki, Yukio
Abstract: Aim: Patients with liver cirrhosis and portosystemic shunt occasionally develop reversed portal flow in the portal venous system. The factors contributing to reversed portal flow in these patients remain unclear. The aim of this study was to identify factors contributing to reversed portal flow in patients with portosystemic shunts based on four‐dimensional computed tomography (4DCT), which visualized flow dynamics in the portal venous system. Methods: Data from 34 consecutive patients with portosystemic shunts who had undergone 4DCT before interventional radiology procedures were retrospectively investigated in this study. Uni‐ and multivariate analyses were performed to identify factors contributing to reversed portal flow. Results: Flow dynamics could be visualized on 4DCT in 32 of the 34 patients. Fifteen patients had forward portal flow; 17 had reversed portal flow. The main portal, splenic, and superior mesenteric veins displayed reversed portal flow in five, 12, and five vessels, respectively. Portosystemic shunt originating from splenic and superior mesenteric veins, worse albumin‐bilirubin score, and small main portal vein diameter were significant factors contributing to reversed portal flow in both univariate ( p  = 0.049, p  = 0.027, and p  = 0.002) and multivariate (odds ratio [OR] 6.345, p  = 0.012; OR 4.279, p  = 0.039; and OR 5.516, p  = 0.019) analyses. Conclusions: The reversed portal flow was visualized on 4DCT. Portosystemic shunt originating distant to the liver, worse albumin‐bilirubin score, and small diameter of the main portal vein were factors contributing to reversed flow in the portal venous system. Abstract : A 65‐year‐old man with gastric varices. Six sequential volume rendering images in a row (a to f), anterior aspect. (a‐c) Early images depict the splenic vein. (d, e) Mid‐phase images additionally depict the portal and left gastric veins. (f) Late image depicts gastric varices, gastrorenal shunt, and the superior mesenteric vein.